Hubungan Kondisi Spiritual Dengan Tingkat Kualitas Hidup Lansia Hipertensi: The Relationship Between Spiritual Condition and Quality of Life Level of Elderly Hypertensive Patients - Wati Wulandari; Rima Berlian Putri; Roza Indra Yeni; Ricky Riyanto Iksan (MPI Press, 2026)
Introduction: Hypertension is a common chronic condition among older adults that can negatively affect their quality of life. In addition to physical factors, psychosocial and spiritual aspects play an important role in helping older adults adapt to their condition. A well-developed spiritual state is associated with better coping mechanisms, emotional stability, and a more positive outlook on life.Objective: This study aimed to determine the relationship between spiritual condition and quality of life among elderly patients with hypertension.Methods: This study used a quantitative analytical observational design with a cross-sectional approach. The population consisted of elderly patients with hypertension, and respondents were selected using a purposive sampling technique based on predetermined inclusion criteria. Data were collected using standardized instruments to measure spiritual well-being and quality of life. Data analysis was conducted using univariate and bivariate methods, and the relationship between variables was tested using the Chi-square test with a predetermined level of significance.Results: The findings indicated that most elderly respondents with better spiritual conditions tended to have better quality of life. Statistical analysis showed a significant relationship between spiritual condition and quality of life, indicating that higher levels of spirituality are associated with improved perceptions of well-being among elderly patients with hypertension.Conclusion: There is a significant relationship between spiritual condition and quality of life among elderly patients with hypertension. These findings emphasize the importance of integrating spiritual assessment and interventions into nursing care as part of a holistic approach to improve the overall well-being of elderly patients.